1990
DOI: 10.1177/070674379003500508
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Disorders and Suicide Attempts in a Prison Population

Abstract: A survey was conducted in which 180 randomly selected male prisoners ages 18 to 44 were interviewed using the Diagnostic Interview Schedule and other questionnaires. A comparison was made with 1,006 similarly aged male residents of Edmonton who were interviewed using the same instruments. Compared to the general population, prisoners were less likely to be married and were less well educated. There was a higher proportion of Native Indians in the prison sample and lower proportions of Oriental and other racial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 12 publications
3
52
0
6
Order By: Relevance
“…The diagnostic criteria for anti-social PD include law-breaking behaviour, which means that this PD overlaps greatly with criminality. Nevertheless, the prevalence of anti-social PD in this survey was comparable with that reported in North American studies of prisoners (Bland et al, 1990;Coté, and Hodgins, 1990). Anti-social PD was strongly associated with borderline PD and substance misuse.…”
Section: Patterns Of Axis II Co-morbidity In Uk Prisonerssupporting
confidence: 87%
See 1 more Smart Citation
“…The diagnostic criteria for anti-social PD include law-breaking behaviour, which means that this PD overlaps greatly with criminality. Nevertheless, the prevalence of anti-social PD in this survey was comparable with that reported in North American studies of prisoners (Bland et al, 1990;Coté, and Hodgins, 1990). Anti-social PD was strongly associated with borderline PD and substance misuse.…”
Section: Patterns Of Axis II Co-morbidity In Uk Prisonerssupporting
confidence: 87%
“…Previous UK studies of psychiatric morbidity in prisoners have either sampled purely remand or sentenced prison populations and focused on the broad category of any PD (Gunn et al, 1991;Brooke et al, 1996;Maden et al, 1994). Meanwhile, North American studies of psychiatric morbidity in prisoners have tended to focus exclusively on anti-social PD (Hare, 1983;Bland et al, 1990;Coté and Hodgins, 1990) or borderline PD (Jordan et al, 1996). This study has a number of strengths, including the use of standardised assessments for the full range of Axis I and II disorders, random sampling to achieve a representative national sample of prisoners, the large sample size and the use of logistic regression to control for the confounding effects of multiple Axis II and Axis I diagnoses.…”
Section: Methodological Issuesmentioning
confidence: 98%
“…So, our sample might have higher levels of psychopathology than prison populations. Despite these differences, however, rates of Thomson et al self-harm among the fire setters in our cohort were similar to those reported in earlier studies of prisoners (Bland et al, 1990;Jenkins et al, 2005;Roy et al, 2014), suggesting that risk of attempted suicide is elevated by factors associated with being an offender rather than fire setting per se. To verify this, a follow-up study to compare suicide attempts between arsonists and prisoners of other types of crimes is needed in the future.…”
Section: Discussionsupporting
confidence: 85%
“…Approximately 14-23% of male prisoners have attempted suicide in their lifetime (Bland et al, 1990;Jenkins et al, 2005;Sarchiapone et al, 2009). According to a study by Roy et al (2014), 13% of a prison sample of 1537 men had a lifetime history of attempted suicide; 6% had made multiple attempts.…”
Section: Introductionmentioning
confidence: 98%
“…Bland found the life-long extensity of psychiatric disorders of prisoners two times more than the general society [10]. There are some other studies showing that the extensity of psychotic disorders on prisoners is similar to the general society as well as the ones which are higher than the general society [11][12][13].…”
Section: Discussionmentioning
confidence: 99%